Digital Al-Quran: A Medium to Assist Students in Practicing Religious Rituals - Maulana, Luthfi; Ardiyansyah, Sendi Maramis; Pratama, Jaka Putra; Romli, Usup (Atthulab: Islamic Religion Teaching and Learning Journal, 2024)
This research aims to explore the potential for using digital Al-Quran in enriching the religious practices of students at the Faculty of Technical and Vocational Education, Indonesian Education University (FPTK UPI). This research adopts a survey research design with a quantitative approach. Data was collected through a questionnaire given to FPTK UPI students, with a focus on the use of the Digital Al-Quran and its impact on their religious practices. Statistical analysis is used to analyze data to gain a deeper understanding. The research results show that the digital Koran positively influences religious practice by providing easy access to religious teachings, increasing understanding, and showing good levels of engagement, confirming its role as a potential tool in enriching students' religious experiences. Thus, the digital Al-Quran is recognized as having great potential to increase religious understanding and religious involvement in higher education environments in Indonesia, especially at FPTK UPI. Penelitian ini bertujuan untuk mengeksplorasi potensi penggunaan Al-Qur’an digital dalam memperkaya praktik keagamaan mahasiswa di Fakultas Pendidikan Teknik dan Kejuruan Universitas Pendidikan Indonesia (FPTK UPI). Penelitian ini mengadopsi desain penelitian survei dengan pendekatan kuantitatif. Data dikumpulkan melalui kuesioner yang diberikan kepada mahasiswa FPTK UPI, dengan fokus pada penggunaan Al-Qur’an Digital dan dampaknya terhadap praktik keagamaan mereka. Analisis statistik digunakan untuk menganalisis data guna mendapatkan pemahaman yang lebih mendalam. Hasil penelitian menunjukkan bahwa Al-Qur’an digital secara positif memengaruhi praktik keagamaan dengan memberikan kemudahan akses terhadap ajaran agama, meningkatkan pemahaman, dan menunjukkan tingkat keterlibatan yang baik, mengkonfirmasi perannya sebagai alat yang berpotensi dalam memperkaya pengalaman keagamaan mahasiswa. Dengan demikian, Al-Qur’an digital diakui memiliki potensi besar untuk meningkatkan pemahaman agama dan keterlibatan keagamaan di lingkungan pendidikan tinggi di Indonesia, khususnya di FPTK UPI.